THE ROLE AND FUNCTION OF LOCAL PEOPLE'S REPRESENTATIVE COUNCIL (DPRD) SUPERVISION IN THE EFFECTIVENESS OF LOCAL GOVERNMENT ADMINISTRATION - Isep H. Insan Insan; Fauzan Azima Faturachman; Kinayah Ashifa; Maudy Anjani; Yustia Okta Pradini (Bengkoelen Justice : Jurnal Ilmu Hukum, 2024)
To realize democratic governance in the regions, the supervisory role of the DPRD is a very important basic tool. In addition to the head of state, the DPRD is the embodiment of the ideals of good governance. Federal and regional development initiatives should be overseen by the DPRD. The DPRD has the opportunity to prove its legitimacy in the eyes of the public and the challenge to prove its authority in carrying out its supervisory duties. Within the framework of effective local governance, this article examines the capacity of the DPRD in carrying out its supervisory responsibilities. The purpose of this study is to find detailed information about the role and function of DPRD supervision in the effectiveness of local government administration which is expected to educate readers on this matter. In this study, the author uses the normative juridical approach method which is carried out based on legal materials by examining theories, legal principles, concepts, and related legislation. Methodologically, we use a normative juridical approach, which is to conduct legal research using law as the basis of norms. Principles, standards, regulations, agreements, and teachings are all part of the relevant norm system. . The purpose of this study is to find detailed information about the role and function of DPRD supervision in the effectiveness of local government administration which is expected to educate readers on this matter. In this study, the author uses the normative juridical approach method which is carried out based on legal materials by examining theories, legal principles, concepts, and related legislation. Methodologically, we use a normative juridical approach, which is to conduct legal research using law as the basis of norms. Principles, standards, regulations, agreements, and teachings are all part of the relevant norm system. Keywords: DPRD, Supervision Function, Local Government